2008
DOI: 10.1002/lpor.200810001
|View full text |Cite
|
Sign up to set email alerts
|

Spectral line‐by‐line shaping for optical and microwave arbitrary waveform generations

Abstract: Spectral line-by-line shaping is a key enabler towards optical arbitrary waveform generation, which promises broad impact both in optical science and technology. In this paper, generation of optical and microwave arbitrary waveforms using the spectral line-by-line shaping technique is reviewed. Compared to conventional pulse shaping, significant new physics arises in the line-by-line regime, where the shaped pulse fields generated from one laser pulse now overlap with those generated from adjacent pulses. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…However, if only the temporal intensity profile is to be controlled leaving the phase unconstrained, as in [18] or in [25], it has been found that with only phase modulation many interesting envelopes can still be synthesized [4], [18], including the RRM at the output of the system. Phase-only shaping is preferred in these cases because of its greater energetic efficiency and also because it only requires the use of one electrooptic phase modulator to perform the shaping.…”
Section: Fundamentals Of the Proposed Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…However, if only the temporal intensity profile is to be controlled leaving the phase unconstrained, as in [18] or in [25], it has been found that with only phase modulation many interesting envelopes can still be synthesized [4], [18], including the RRM at the output of the system. Phase-only shaping is preferred in these cases because of its greater energetic efficiency and also because it only requires the use of one electrooptic phase modulator to perform the shaping.…”
Section: Fundamentals Of the Proposed Techniquementioning
confidence: 99%
“…Optical pulse shaping techniques have, consequently, received an increasing attention in the last few years [4]- [6]. Of specific interest are techniques for pulse repetition rate multiplication (RRM), which are used to generate ultrafast optical pulse trains from a low repetition rate input pulse train [7]- [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, repetition-rate scale up of periodic pulse sources is significantly important for the increasing demand in ultrahigh-speed optical communications. One of the most appealing methods for scaling up the pulse rate is to multiply the repetition rate of a lower rate source [21][22][23][24][25][26][27][28]. Therefore, discovering a technique to multiply the repetition rate of a compact self-mode-locked laser will be greatly prospective for generating ultrahighrepetition-rate sources.…”
Section: Introductionmentioning
confidence: 99%